Positive plate and battery

By setting the concave and convex areas on the active material layer of the positive electrode sheet and optimizing the adhesive content, the problem of insufficient electrolyte during the charge and discharge cycle of the battery is solved, and the cycle life and energy density of the battery are improved.

CN119650580APending Publication Date: 2025-03-18ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411832296.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the charging and discharging cycle, existing batteries are prone to insufficient electrolyte and poor infiltration, resulting in rapid attenuation of battery capacity or lithium separation.

Method used

Concave and convex areas are arranged on the active material layer of the positive electrode sheet to form a local micro gap to store more electrolyte, and by optimizing the binder content and compaction density, the weight loss rate of the positive electrode sheet is controlled to be in the range of 1.1% to 6%.

Benefits of technology

The cycle life and energy density of the battery are improved, and the insufficient electrolyte and poor infiltration problems between the positive electrode and the separator are avoided, while delaying the fatigue of the negative electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650580A_ABST
    Figure CN119650580A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and provides a positive plate and a battery, the positive plate comprises a positive current collector and a positive active material layer arranged on the surface of the positive current collector, the positive active material layer comprises a positive active material, and the positive active material layer comprises a concave-convex region, the positive electrode active material layer is provided with a concave-convex area, the concave-convex area comprises a plurality of concave parts and convex parts arranged corresponding to the concave parts, in a nitrogen environment, the weight loss ratio of the positive electrode active material layer within the temperature range of 35 DEG C to 450 DEG C is rho, and the rho is 1.1%-6%. According to the embodiment of the invention, the cycle life of the battery can be prolonged, the structural stability of the positive plate is high, the problems of powder falling and the like of the positive plate can be prevented, and the positive plate can be prevented from being damaged in the process of forming the concave-convex region on the basis of ensuring the energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet and a battery. Background Art

[0002] Batteries are usually constructed into a layered structure including multiple pole pieces. Extrusion will occur between different layers of the battery or between different parts of the same layer, and when the battery undergoes a charge and discharge cycle, the pole pieces will expand, thereby aggravating the above-mentioned extrusion. This extrusion will destroy the stability of the battery's layered structure, making the battery prone to local electrolyte deficiency, poor wetting, and interface deterioration, and may even lead to rapid decay of battery capacity or safety problems such as lithium deposition. Summary of the invention

[0003] The present application provides a positive electrode sheet and a battery, which can solve the technical problems of insufficient electrolyte between layers and poor wetting in the above-mentioned prior art, which may cause rapid attenuation of battery capacity or lithium precipitation, while ensuring the stability of its structure.

[0004] The first aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material.

[0005] The positive electrode active material layer includes a concavo-convex region, wherein the concavo-convex region includes a plurality of concave portions and convex portions arranged corresponding to the concave portions.

[0006] In a nitrogen environment, the weight loss rate of the positive electrode active material layer in the temperature range from 35° to 450° C. is ρ, and the ρ satisfies: 1.1% to 6%.

[0008] According to the positive electrode sheet described in the first aspect of the present application, since a concave-convex area is provided on the positive electrode active material layer, a local microgap can be formed between the positive electrode sheet and the negative electrode sheet, thereby providing spatial conditions for storing more electrolyte, being able to provide more electrolyte for a long cycle of the battery, improving the wetting ability of the electrolyte in this area, avoiding abnormal situations such as insufficient electrolyte and poor wetting between the positive electrode and the diaphragm, thereby improving the cycle life of the battery; moreover, by forming a concave-convex area, the surface of the positive electrode sheet is made uneven, so that when the battery cell expands, the convex part can effectively support the diaphragm, thereby preventing the diaphragm from being deformed by the expansion stress of the negative electrode sheet.

[0009] A convex portion is provided on the positive electrode sheet to improve the deformation capacity of the positive electrode sheet. When the positive electrode sheet contacts the expanded negative electrode sheet, the convex portion on the positive electrode sheet can effectively absorb the expansion stress of the negative electrode sheet, which can buffer the expansion of the negative electrode sheet during the battery cycle and avoid the excessive expansion stress of the negative electrode sheet and cracks. In addition, the convex portion provided on the positive electrode sheet can absorb part of the expansion stress of the negative electrode sheet, so that the negative electrode sheet does not completely rely on the resistance of its own material when expanding, delaying the fatigue of the negative electrode material, thereby increasing the service life of the negative electrode sheet.

[0010] In addition, since the weight loss rate of the positive electrode sheet is set in the above range, the weight loss rate is used to reflect the structural stability of the positive electrode sheet, and to prevent the binder in the positive electrode active material layer from being stretched due to excessive pressure in forming the concave-convex area on the positive electrode sheet, thereby reducing the effect of the binder connecting the positive electrode active particles, or the compaction density during rolling is too large, or the content of the binder in the positive electrode active material layer is too small, resulting in excessive force on the positive electrode active material layer and powder falling. In addition, excessive content of the binder will not only affect the energy density of the positive electrode sheet, but also the overall structure of the positive electrode sheet with too much binder will become brittle, hard, and have poor overall toughness, resulting in the positive electrode sheet not being stretched as a whole in the process of forming the concave-convex area, and the stress is too concentrated and easily crushed; that is, by balancing the compaction density of the positive electrode sheet, the content of the binder, and the height of the convex point, the weight loss rate of the positive electrode sheet is controlled within this range, and the positive electrode sheet can be prevented from being damaged in the process of forming the concave-convex area on the basis of ensuring the energy density.

[0011] In a possible implementation, the height of the vertex of the protrusion from the surface of the positive electrode active material layer is h, and h and ρ satisfy the relationship:

[0012] 50<h / ρ<3600, and / or h=3um~40um.

[0013] In a possible implementation, the diameter of the convex portion is R, the distance between two adjacent convex portions is L, and R, L, and ρ satisfy the relationship:

[0014] 10<L / R / ρ<1000, and / or R=1000um~5000um, and / or L=1500um~5000um.

[0015] In a possible implementation, the compaction density of the positive electrode sheet is D, and D, h, and R satisfy the relationship:

[0016] 0.004<D*h / R<0.12, and / or D=3g / cm 3 ~4.5g / cm 3 .

[0017] In a possible implementation, the number of the convex parts or the concave parts in the concave-convex region per unit area is N / cm 2 , said N=2~25, preferably, said N=4~15.

[0018] In a possible implementation, the positive electrode active material layer includes a conductive agent, the conductive agent includes single-walled carbon nanotubes, and the single-walled carbon nanotubes extend into the positive electrode active material in the top of the protrusion.

[0019] In a possible implementation, two adjacent convex portions respectively form a first projection and a second projection, the first projection has a first circumscribed circle, the second projection has a second circumscribed circle, the distance between the center of the first circumscribed circle and the center of the second circumscribed circle is L1, the distance between the first projection and the second projection is L2, and L1 and L2 satisfy the relationship:

[0020] L1 / L2=1.05~3, preferably, L1 / L2=1.1~2.

[0021] In a possible implementation, L1=3mm-10mm, preferably, L1=2mm-8mm;

[0022] And / or, L2=0.5mm~8mm, preferably, L2=1mm~4mm.

[0023] In a possible implementation, the convex portion has a circumscribed sphere, the circumscribed sphere includes an outer surface, a straight area is formed between two adjacent convex portions, the spherical radius of the outer surface is R1, and the distance between the top of the convex portion and the straight area is R3, and R3 satisfies the relationship:

[0024] R3<R1, preferably, R3<1 / 5R1.

[0025] In one possible implementation, the surface area of ​​the outer surface is Q1, and the projected area of ​​the outer surface formed on the positive electrode current collector along the thickness direction of the pole piece is S1. The circumscribed sphere also includes an inner surface, and the surface area of ​​the inner surface is Q2. The projected area of ​​the inner surface formed on the positive electrode current collector along the thickness direction of the pole piece is S2. Q1 and Q2 satisfy: Q1 / Q2=1.02~1.21, and / or S1 and S2 satisfy: S1 / S2=1.02~1.21.

[0026] In a possible implementation, the sum of the projected areas of the protrusions on the positive electrode current collector is S11, the area of ​​the positive electrode sheet is S, and S11 and S satisfy the relationship:

[0027] 0.02≤S11 / S≤0.85.

[0028] In a possible implementation, the single-walled carbon nanotubes are interwoven to form a network structure, and the positive electrode active material on the top of the protrusion is wrapped in the network structure.

[0029] In one possible implementation, the diameter of the single-walled carbon nanotube is 1nm~1000nm, and the length is 1um~100um; and / or the mass percentage of the single-walled carbon nanotube is 0.5%~5% based on the total mass of the positive electrode active material layer; and / or the thickness of the single-walled carbon nanotube on the positive electrode active material layer is 10nm~500nm.

[0030] In one possible implementation, the positive electrode active material includes a binder, and the mass percentage of the binder is: 1-5wt% based on the total mass of the positive electrode active material layer; and / or the binder includes at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.

[0031] A second aspect of the present application provides a battery, comprising a diaphragm, a negative electrode sheet, and a positive electrode sheet as described in any one of claims 1 to 13, wherein the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, and the diaphragm, the positive electrode sheet and the negative electrode sheet are wound along the length direction of the positive electrode sheet to form a core structure.

[0032] In a possible implementation, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes a silicon-carbon composite material and / or a silicon-oxygen composite material.

[0033] In a possible implementation, the dimension of the convex portion along the thickness direction of the positive electrode sheet is h3, and the dimension of the concave portion along the thickness direction of the positive electrode sheet is h4, and the h3 and h4 satisfy the relationship:

[0034] h3 / h4=0.2~1. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art description are briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 A schematic diagram of the structure of a battery provided according to an embodiment of the present application is shown;

[0037] Figure 2 A schematic diagram of the structure of a positive electrode sheet provided according to an embodiment of the present application is shown;

[0038] Figure 3 A schematic structural diagram of a convex portion provided according to an embodiment of the present application is shown;

[0039] Figure 4 A schematic diagram showing the structure of two adjacent protrusions of a positive electrode sheet provided according to an embodiment of the present application is shown;

[0040] Figure 5 A side view of a positive electrode sheet provided according to an embodiment of the present application is shown.

[0041] Reference numerals:

[0042] 100-positive electrode sheet; 110-positive electrode current collector; 120-positive electrode active material layer; 130-positive electrode ear; 101-concave-convex area; 102-convex part; 103-concave part; 104-ear area; 105-end avoidance area; 106-double-sided area; 107-single-sided area; 108-head end; 109-tail end; 1051-first avoidance area; 1052-second avoidance area;

[0043] 200-negative electrode sheet; 210-negative electrode current collector; 220-negative electrode active material layer;

[0044] 300-Diaphragm. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0046] With the rapid development of lithium-ion batteries, the market has put forward higher requirements on the performance of lithium-ion batteries. For example, when lithium-ion batteries are used in new energy vehicles, they need to have better charging rate, cycle life and safety. For another example, when lithium-ion batteries are used in household appliances such as desk lamps and shavers or electronic devices such as mobile phones and tablets, they need to have higher energy density.

[0047] In recent years, new energy technologies are in a rapid development stage, and lithium-ion batteries are also in a stage of rapid development. Lithium-ion batteries are constantly being optimized and innovated in terms of material selection, process manufacturing, and structural design. When designing lithium-ion batteries, they mainly face capacity issues, safety issues, and life issues. With the continuous exploration of materials, processes, and structures, lithium-ion batteries have also been continuously improved in terms of performance, which is mainly reflected in the advantages of lithium-ion batteries such as high energy density, long cycle life, and high safety. Therefore, lithium-ion batteries are often used in new energy fields, portable consumer electronics, wearable electronic devices, and many other fields.

[0048] The quality of battery performance, such as cycle life, energy density, and safety, mainly depends on the material selection of relevant components in the battery, the manufacturing process of each component, the structure of each component, and the related connection design between the components. The performance of the battery can be improved by optimizing and upgrading the materials, manufacturing process, structure, and connection design. Material selection and manufacturing process are related to the progress of some underlying technologies and underlying sciences such as physics and chemistry. At the current stage of battery development, it is difficult to optimize and upgrade materials and manufacturing processes. The structure and connection design of the battery are in constant upgrading and transformation. Therefore, in order to improve the performance of the battery, at the current stage when the development of materials and manufacturing processes is hindered, the structure and connection design of the battery can be optimized to achieve the purpose of improving the performance of the battery.

[0049] Unless otherwise specified, the battery described in the present application may be a lithium-ion battery, which may be designed as a stacked structure or a wound core structure. Both the stacked structure and the wound core structure are hierarchical structures. The stacked structure is formed by stacking multiple pole pieces and diaphragms to form a hierarchical structure, and the wound core structure is formed by winding pole pieces and diaphragms in multiple circles clockwise or counterclockwise to form a hierarchical structure. The pole pieces here may include positive pole pieces and negative pole pieces.

[0050] During the manufacturing process of the battery, for example, when forming the above-mentioned stacked structure and wound core structure batteries, the battery is usually constructed into a hierarchical structure including a plurality of pole pieces. Extrusion will occur between different layers of the battery or between different parts of the same layer, and when the battery undergoes a charge and discharge cycle, the pole pieces will expand, thereby aggravating the above-mentioned extrusion. Such extrusion will break the stability of the hierarchical structure of the battery, making the battery prone to local electrolyte deficiency, poor wetting, and interface deterioration, and may even lead to rapid decay of the battery capacity or safety problems such as lithium plating.

[0051] Based on the above status quo and problems, an embodiment of the present application provides a positive electrode sheet, which can solve the technical problems of insufficient electrolyte between layers and poor wetting in the above-mentioned prior art, which may cause rapid attenuation of battery capacity or lithium precipitation, while ensuring its structural stability.

[0052] The positive electrode sheet in the embodiment of the present application changes the design concept of the fitting between the electrode sheets. By reasonably arranging supporting structures such as concave and convex parts on the positive electrode sheet and combining the content of the adhesive in the positive electrode active material layer, a local micro gap can be formed between the positive electrode sheet and the negative electrode sheet on the basis of ensuring the overall structural strength and structural stability, thereby providing spatial conditions for storing more electrolyte, and being able to provide more electrolyte for the long cycle of the battery, thereby improving the cycle life of the battery. In addition, the embodiment of the present application can also improve the energy density of the battery by reasonably configuring the material ratio of the positive electrode active material layer on the positive electrode sheet, while also preventing the positive electrode sheet from being damaged in the process of forming the concave and convex areas.

[0053] Figure 1 A schematic structural diagram of a battery provided according to an embodiment of the present application is shown.

[0054] This application embodiment provides a battery, please refer to Figure 1 The battery includes a positive electrode sheet 100, a negative electrode sheet 200 and a separator 300. The separator 300 is arranged between the positive electrode sheet 100 and the negative electrode sheet 200. The separator 300, the positive electrode sheet 100 and the negative electrode sheet 200 are wound along the length direction of the positive electrode sheet 100 to form a core structure.

[0055] The positive electrode sheet 100 in the battery can be the positive electrode sheet 100 with the concave portion 103 and the convex portion 102 as mentioned above, and the content of the adhesive on the positive electrode sheet 100 is also optimized. Based on the setting of the positive electrode sheet 100, the battery has excellent performance stability, and can also improve the energy density and cycle life of the battery.

[0056] The positive electrode sheet 100 may include a positive electrode current collector 110 and a positive electrode active material. The positive electrode current collector 110 may be made of aluminum foil or other commonly used positive electrode current collectors 110. The thickness of the positive electrode current collector 110 may be set according to actual needs. In some embodiments, to ensure the toughness of the positive electrode sheet 100, the thickness of the positive electrode current collector 110 may be designed in association with the thickness of the positive electrode active material. The positive electrode active material may be coated on one surface or both surfaces of the positive electrode current collector 110.

[0057] The positive electrode active material generally adopts a lithium-containing material, for example, the positive electrode active material can be at least one of lithium cobalt oxide, lithium manganate, lithium iron phosphate, lithium manganese iron phosphate, nickel cobalt manganate, nickel cobalt aluminum oxide, ternary or nickel manganate. The positive electrode active material also includes a binder and a conductive agent. The binder in the positive electrode active material may include polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, a polyamide, a polyacrylonitrile, a polyacrylate, a polyacrylic acid, a polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinyl pyrrolidone, a polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, flake graphite, graphene, carbon nanotubes or carbon fibers. In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the binder is: 1-5wt%.

[0058] The negative electrode sheet 200 may include a negative electrode current collector 210 and a negative electrode active material. The negative electrode current collector 210 may be made of copper foil or other commonly used negative electrode current collectors 210. The thickness of the negative electrode current collector 210 may be set according to actual needs. In some embodiments, in order to ensure the toughness of the negative electrode sheet 200, the thickness of the negative electrode current collector 210 may be designed in association with the thickness of the negative electrode active material. The negative electrode active material may be coated on one surface or both surfaces of the negative electrode current collector 210.

[0059] The negative electrode active material may include one of graphite or silicon-based materials, the latter of which may provide higher energy density, and the silicon-based material may include at least one of silicon, silicon oxide, silicon carbon compound or silicon alloy. Conductive agent and / or binder may also be included. Exemplarily, the conductive agent in the negative electrode active material may include at least one of carbon black, acetylene black, Ketjen black, flake graphite, graphene, carbon nanotubes, carbon fibers or carbon nanowires. The binder in the negative electrode active material may include at least one of carboxymethyl cellulose CMC, polyacrylic acid, polyacrylic acid salt, polyacrylic acid ester, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin or polyfluorene.

[0060] In the above-mentioned positive electrode sheet 100, the positive electrode active material and its conductive agent and adhesive can form an integral structure and be coated on at least one surface of the positive electrode collector 110. For the convenience of description, the integral structure can be the positive electrode active material layer 120. In the above-mentioned negative electrode sheet 200, the negative electrode active material and its conductive agent and adhesive can form an integral structure and be coated on at least one surface of the negative electrode collector 210. For the convenience of description, the integral structure can be the negative electrode active material layer 220.

[0061] In some embodiments, the negative electrode sheet 200 includes a negative electrode current collector 210 and a negative electrode active material layer 220 . The negative electrode active material layer 220 may include a silicon-carbon composite material and / or a silicon-oxygen composite material.

[0062] The silicon content in the silicon-carbon composite material and / or the silicon-oxygen composite material is relatively high. The negative electrode active material layer 220 includes the silicon-carbon composite material and / or the silicon-oxygen composite material, which can improve the energy density of the battery.

[0063] The silicon-carbon composite material may include a porous carbon matrix, silicon grains in the pores of the porous silicon matrix, and a carbon layer on the surface of the porous carbon matrix. The material of the carbon layer may be shaped carbon or amorphous carbon. In some embodiments, the carbon layer may include openings arranged corresponding to the pores of the porous silicon matrix.

[0064] In this way, by providing openings on the carbon layer corresponding to the pores of the porous silicon substrate, the wettability of the electrolyte to the negative electrode active material can be improved, while the expansion performance of silicon can be reduced, the cycle life of the battery cell can be improved, and the service life of the battery can be increased.

[0065] In some embodiments, the material of the negative electrode active layer 31 may also include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, graphene, soft carbon, hard carbon, soft carbon-coated graphite material, and hard carbon-coated graphite material.

[0066] In some embodiments, the specific surface area of ​​the silicon-carbon composite material is 0.5 m 2 / g-10m 2 / g, for example, the specific surface area of ​​the silicon-carbon composite material can be 0.5m 2 / g, 0.9m 2 / g, 1.3m 2 / g, 1.5m 2 / g, 1.85m 2 / g, 2.0m 2 / g, 2.3m 2 / g, 2.7m 2 / g, 3.2m 2 / g, 3.6m 2 / g, 3.8m 2 / g, 4.6m 2 / g, 4.8m 2 / g, 5.1m 2 / g, 5.4m 2 / g, 5.8m 2 / g, 6.1m 2 / g, 6.5m 2 / g, 6.8m 2 / g, 7.2m 2 / g, 7.5m 2 / g, 7.8m 2 / g, 8.3m 2 / g, 8.9m 2 / g, 9.4m 2 / g and 9.9m 2 Alternatively, the specific surface area of ​​the silicon-carbon composite material may be greater than or equal to 0.5 m 2 / g and less than or equal to 10m 2 Any value within the range of / g.

[0067] In this way, by controlling the specific surface area in the silicon-carbon composite material, the solid electrolyte interface (SEI) film during the charging process can be reduced, and the cycle performance and service life can be improved. It can avoid the situation where the thickness of the SEI film is too small due to the small specific surface area, thereby failing to effectively isolate the electrolyte and the negative electrode active layer 31. It can also avoid the SEI film being too large due to the large specific surface area, and can reduce the impact of the SEI film being too thick on the capacity and efficiency of the battery.

[0068] In some embodiments, the particle size Dv50 of the silicon-carbon composite material is 6 μm-15 μm, for example, it can be one of 6 μm, 7 μm, 8 μm, 9 μm, 11 μm, 13 μm and 14 μm, or it can be any point value within the range of 6 μm or more and 15 μm or less.

[0069] Thus, by controlling the particle size of the silicon-carbon composite material within the above range, it is possible to avoid the situation where the specific surface area of ​​the silicon particles is increased when the particle size is too small, thereby increasing the side reactions. It is also possible to avoid the problem where the silicon particles are easily expanded too much when the particle size is too large, thereby blocking the pores of the porous carbon matrix and affecting the infiltration of the electrolyte.

[0070] The average sphericity of the silicon-carbon material is in the range of 0.5-1, for example, the average sphericity can be one of 0.6, 0.7, 0.8 and 0.9. Compared with non-spherical particles, the higher the sphericity, the closer the shape is to a sphere, so that when its volume expands, the impact on the structure of the negative electrode sheet 30 is smaller, and the overall structural stability of the negative electrode sheet 30 can be maintained during expansion.

[0071] In addition, spherical particles can improve the mechanical strength and stability of the material and reduce the stress concentration between particles caused by expansion, thereby reducing the risk of mechanical wear and damage to the material during the cycle.

[0072] In some embodiments, the powder resistivity of the silicon-carbon composite material ranges from 0.1Ω·cm to 1000Ω·cm. For example, the powder resistivity of the silicon-carbon composite material may be one of 0.1Ω·cm, 0.9Ω·cm, 1.2Ω·cm, 1.3Ω·cm, 1.8Ω·cm, 2.7Ω·cm, 4.6Ω·cm, 7.8Ω·cm, 11Ω·cm, 25Ω·cm, 38Ω·cm, 60Ω·cm, 100Ω·cm, 200Ω·cm, 300Ω·cm, 400Ω·cm, 500Ω·cm, 600Ω·cm, 700Ω·cm, 800Ω·cm, 900Ω·cm and 1000Ω·cm. Alternatively, the powder resistivity of the silicon-carbon composite material may be any point value within the range of greater than or equal to 0.1Ω·cm and less than or equal to 1000Ω·cm.

[0073] In some embodiments, the silicon content in the silicon-carbon composite material may be 30%-75%, for example, the silicon content in the silicon-carbon composite material may be one of 30%, 35%, 41%, 45%, 49%, 51%, 55%, 59%, 61%, 64%, 71% and 84%. Alternatively, the silicon content in the silicon-carbon composite material may be any point value within the range of greater than or equal to 30% and less than or equal to 75%.

[0074] In this way, it is possible to avoid excessive silicon content in the negative electrode active layer 31 causing excessive expansion of the negative electrode sheet, thereby deforming the overall structure of the silicon-carbon particles, and to avoid too little silicon content reducing the energy density of the battery.

[0075] In some embodiments, the dimension of the protrusion 102 on the positive electrode sheet 100 along the thickness direction of the positive electrode sheet 100 is h3, and the dimension of the concave portion 103 along the thickness direction of the positive electrode sheet 100 is h4, and h3 and h4 satisfy the relationship: h3 / h4=0.2~1.

[0076] Please refer to Figure 1In the thickness direction of the positive electrode sheet 100, the convex portion 102 and the concave portion 103 are formed on different sides of the positive electrode sheet 100, and the convex portion 102 and the concave portion 103 are arranged correspondingly. At a certain position of the positive electrode sheet 100, the convex portion 102 is located on one side of the positive electrode sheet 100, and the concave portion 103 is located on the other side of the positive electrode sheet 100. In the above embodiment, the size h3 of the convex portion 102 is set to be less than or equal to the size h4 of the concave portion 103. Based on the existence of the concave portion 103, sufficient local micro-gap can be formed between the positive electrode sheet 100 and the negative electrode sheet 200. The small size design of the convex portion 102 can avoid the enlargement of the battery size in the thickness direction, and can provide more electrolyte storage space on the basis of ensuring the energy density of the battery, thereby achieving a balance between the energy density and the cycle life of the battery; and the smaller size of the convex portion 102 can prevent the positive electrode sheet 100 from being broken due to excessive pressure when the convex portion is formed on the positive electrode sheet 100. During specific design, h3 / h4 can be 0.2, 0.4, 0.6, 0.8, 1 or a range consisting of any two of them.

[0077] Figure 2 A schematic structural diagram of a positive electrode sheet provided according to an embodiment of the present application is shown.

[0078] Please refer to Figure 1 and 2 The positive electrode sheet 100 includes the aforementioned positive electrode collector 110 and a positive electrode active material layer 120 arranged on the surface of the positive electrode collector 110, the positive electrode active material layer 120 includes a positive electrode active material, and the positive electrode active material layer 120 includes a concave-convex area 101, the concave-convex area 101 includes a plurality of concave portions 103 and convex portions 102 arranged corresponding to the concave portions 103. In a nitrogen environment, the weight loss rate of the positive electrode active material layer 120 in the temperature range from 35° to 450°C is ρ, and ρ satisfies: 1.1% to 6%.

[0079] In some specific embodiments, the concave-convex area is formed by punching the active material layer of the electrode sheet. By punching the positive electrode active material layer 120 of the positive electrode sheet, the electrode sheet is deformed, thereby improving the overall deformation capacity of the positive electrode sheet.

[0080] It should be noted that the above-mentioned weight loss rate can be obtained through TGA testing. When conducting TGA testing, some materials will be carbonized and decomposed by heat, which will cause a loss in mass of the positive electrode sheet 100, thereby causing the above-mentioned weight loss phenomenon. The weight loss rate indicates the quantitative proportion of the mass reduction of the positive electrode sheet 100 during the high-temperature test.

[0081] In the above embodiment, the weight loss rate of the positive electrode sheet is set in the above range. The weight loss rate is used to reflect the structural stability of the positive electrode sheet. The weight loss rate is affected by factors such as the compaction density of the positive electrode sheet, the height of the protrusions, and the content of the binder. By controlling the weight loss rate, it is prevented that in the process of forming the concave-convex area on the positive electrode sheet, the binder in the positive electrode active material layer is stretched due to excessive pressure to form the concave-convex area, thereby reducing the effect of the binder connecting the positive electrode active particles, or the compaction density is too high during the rolling process, or the content of the binder in the positive electrode active material layer is too small, which causes the positive electrode active particles to be stretched. The material layer is subjected to excessive force and powdering occurs. In addition, too much binder content will not only affect the energy density of the positive electrode sheet, but also the overall structure of the positive electrode sheet with a large weight loss rate will become brittle, hard, and have poor overall toughness, resulting in the positive electrode sheet as a whole not being stretched in the process of forming the concave and convex area, and the stress is too concentrated and easily crushed; that is, by balancing the compaction density of the positive electrode sheet, the content of the binder, the height of the convex point and other factors, the weight loss rate of the positive electrode sheet is controlled within this range, and the positive electrode sheet can be prevented from being damaged in the process of forming the concave and convex area on the basis of ensuring the energy density.

[0082] In specific design, the weight loss rate ρ may be 1.1%, 1%, 2%, 3%, 4%, 5%, 6% or a range consisting of any two of them.

[0083] In the embodiment of the present application, since the concave-convex area 101 is provided on the positive electrode active material layer 120, a local microgap can be formed between the positive electrode sheet 100 and the negative electrode sheet 200, thereby providing spatial conditions for storing more electrolyte, and being able to provide more electrolyte for the long cycle of the battery, thereby improving the wetting ability of the electrolyte in this area, avoiding abnormal situations such as insufficient electrolyte and poor wetting between the positive electrode and the diaphragm, thereby improving the cycle life of the battery; moreover, by forming the concave-convex area, the surface of the positive electrode sheet is made uneven, so that when the battery cell expands, the convex part can effectively support the diaphragm, thereby preventing the diaphragm from being deformed by the expansion stress of the negative electrode sheet.

[0084] In addition, a convex portion is provided on the positive electrode sheet to improve the deformation capacity of the positive electrode sheet. When the positive electrode sheet contacts the expanded negative electrode sheet, the convex portion on the positive electrode sheet can effectively absorb the expansion stress of the negative electrode sheet, which can buffer the expansion of the negative electrode sheet during the battery cycle and avoid the excessive expansion stress of the negative electrode sheet and the occurrence of cracks. Moreover, the convex portion provided on the positive electrode sheet can absorb part of the expansion stress of the negative electrode sheet, so that the negative electrode sheet does not completely rely on the resistance of its own material when expanding, delaying the fatigue of the negative electrode material, thereby increasing the service life of the negative electrode sheet.

[0085] Figure 3 A schematic structural diagram of a convex portion provided according to an embodiment of the present application is shown; Figure 4A schematic structural diagram of two adjacent protrusions of a positive electrode sheet provided according to an embodiment of the present application is shown.

[0086] In some embodiments, please refer to Figure 3 The height of the top of the protrusion 102 from the surface of the positive electrode active material layer 120 is h, and h and ρ satisfy the relationship: 50<h / ρ<3600, and / or h=3um~40um.

[0087] It can be understood that the larger the size of h, that is, the higher the apex of the convex portion, means that when the convex portion 102 is formed, the greater the stress on the positive electrode sheet will be, that is, the higher the probability of the positive electrode active material in the positive electrode sheet being de-powdered due to the force, and the higher the apex of the convex portion, the easier it is for the positive electrode active material at the apex of the convex portion to crack or fall off, and it is easy to pass through the diaphragm and contact the negative electrode sheet to cause self-discharge; at this time, combined with the weight loss rate (that is, the content of the binder), a good combination relationship can be formed, that is, the structural stability of the convex portion 102 can be ensured, and problems such as powdering of the positive electrode active material layer or breakage of the positive electrode sheet can be prevented, and the positive electrode active material at the apex can be prevented from falling off, and the adhesive content can be prevented from being too poor due to the poor toughness of the positive electrode sheet, which is easy to be crushed under pressure, and the silicon-doped negative electrode sheet can be prevented from drastically expanding during the charge and discharge process, thereby squeezing the convexity of the positive electrode sheet to cause it to collapse and deform, and preventing it from affecting the energy density. In the specific design, h / ρ can be 50, 200, 400, 600, 800, 1200, 1400, 1600, 1800, 2400, 3000, 3200, 3400, 3600 or a range consisting of any two of them, and h can be 3um, 10um, 20um, 30um, 40um or a range consisting of any two of them.

[0088] In some embodiments, please refer to Figure 4 , the diameter of the protrusion 102 is R, the distance between two adjacent protrusions 102 is L, R, L, ρ satisfy the relationship: 10<L / R / ρ<1000, and / or R=1000um~5000um, and / or L=1500um~5000um.

[0089] It can be understood that L / R can reflect the density of the protrusions 102 on the positive electrode current collector 110, and the density is related to the value of the weight loss rate. The greater the density, the more protrusions 102, which is more conducive to the infiltration of the electrolyte and the improvement of the cycle life. However, if L / R is too large, that is, the protrusions are too dense, it is easy to cause the stress to be too dense in the process of forming the protrusions 102, and it is difficult to effectively release the stress. The positive active material layer of the positive electrode sheet 100 is more likely to lose powder, and even the positive electrode sheet will break, and the toughness requirement for the positive electrode sheet will be higher; here, setting L / R / ρ in the above range is conducive to achieving a balance between density and weight loss rate. By controlling the ratio of the density of the embossed depressions to the weight loss rate, that is, controlling the density of the embossed protrusions, while ensuring the energy density, when the protrusions of the positive electrode or the protruding part of the positive electrode are subjected to force, the protrusions within this ratio range can effectively disperse the stress on the protrusions and prevent cracks or powder loss. During the specific design, L / R / ρ can be 10, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000 or a range formed by any two of them, R can be 1000um, 2000um, 3000um, 4000um, 5000um or a range formed by any two of them, and L can be 1500um, 2000um, 3000um, 4000um, 5000um or a range formed by any two of them.

[0090] In some embodiments, the compaction density of the positive electrode sheet 100 is D, and D, h, and R satisfy the relationship: 0.004<D*h / R<0.12, and / or D=3g / cm 3 ~4.5g / cm 3 .

[0091] It should be noted that the compaction density D of the positive electrode sheet 100 = (mass of the positive electrode sheet - mass of the positive electrode collector) / [surface area of ​​the positive electrode sheet (single-sided area) * (thickness of the positive electrode sheet - thickness of the positive electrode collector)].

[0092] The compaction density of the positive electrode sheet 100 indicates the compactness of the particles in the positive electrode active material layer 120. h / R can reflect the size of the above particles. The greater the compaction density of the positive electrode sheet, the tighter the combination of the active material. For the same size embossing, the height of the convex part decreases with the increase of the compaction density. Continuing to increase the height of the convex part may cause the risk of the positive electrode sheet breaking. By seeking a balance between the compaction density and the size of the particles, the structural stability of the positive electrode sheet 100 can be improved, which is conducive to forming the above-mentioned concave-convex area 101 on the positive electrode sheet 100 and preventing the positive electrode sheet 100 from breaking. In the specific design, D*h / R can be 0.004, 0.008, 0.012, 0.016, 0.036, 0.056, 0.076, 0.1, 0.12 or a range consisting of any two of them. D can be 3g / cm 3 、3.5g / cm 3 , 4g / cm 3 4.5g / cm 3 Or a range consisting of any two of them.

[0093] In some embodiments, the number of convex portions 102 or concave portions 103 per unit area of ​​the concave-convex region 101 is N / cm 2 , N=2~25, preferably, N=4~15.

[0094] The value of N can reflect the density of the protrusions 102. Setting N within the above range can reasonably balance the cycle life and energy density of the battery. At the same time, it can also ensure the structural stability of the positive electrode sheet 100 and prevent the protrusions from being too dense. In the process of forming the protrusions, the positive electrode sheet 100 is subjected to excessive force and breaks.

[0095] In some embodiments, the positive electrode active material layer includes a conductive agent, the conductive agent includes single-walled carbon nanotubes, and the single-walled carbon nanotubes extend into the positive electrode active material in the top of the protrusion 102 .

[0096] It can be understood that after the protrusion 102 is formed, the gap between the particles at the top of the protrusion 102 is larger than the gap between the particles at other positions of the protrusion 102. By setting the conductive agent including single-walled carbon nanotubes, a single carbon nanotube can linearly connect adjacent positive electrode active materials. Moreover, during the embossing process, the single-walled carbon nanotube can adapt to stress and undergo tensile deformation, always maintaining connection with adjacent positive electrode active materials, thereby ensuring the conductive performance between the particles at the top of the protrusion 102.

[0097] In some specific embodiments, the single-walled carbon nanotubes are interwoven to form a network structure, and the positive electrode active material on the top of the protrusion 102 is wrapped in the network structure.

[0098] Arranging the single-walled carbon nanotubes into a mesh structure is conducive to achieving better contact between the particles and the single-walled carbon nanotubes, and can also increase the contact area between the particles and the single-walled carbon nanotubes, thereby improving the conductivity between the particles at the top of the protrusion 102 .

[0099] In some specific embodiments, the diameter of the single-walled carbon nanotube is 1nm~1000nm, and the length is 1um~100um; and / or the mass percentage of the single-walled carbon nanotube is 0.5%~5% based on the total mass of the positive electrode active material layer 120; and / or the thickness of the single-walled carbon nanotube on the positive electrode active material layer 120 is 10nm~500nm.

[0100] In the above embodiment, the content and size of the single-walled carbon nanotubes in the positive electrode active material layer 120 can be limited in terms of diameter, length, mass percentage and thickness. By setting the diameter, length, mass percentage and thickness of the single-walled carbon nanotubes within the above range, the positive electrode sheet 100 in the above embodiment can be better matched, so that the basic performance of the positive electrode sheet 100 can be guaranteed under the condition of improving the conductivity between the particles at the top of the protrusion 102. The basic performance here includes the structural stability, cycle life and energy density mentioned above.

[0101] In the specific design, the diameter of the single-walled carbon nanotube can be 1nm, 100nm, 500nm, 1000nm or a range consisting of any two thereof; the length of the single-walled carbon nanotube can be 1um, 10um, 30um, 50um, 70um, 90um, 100um or a range consisting of any two thereof; the mass percentage of the single-walled carbon nanotube can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%; the thickness of the single-walled carbon nanotube can be 10nm, 200nm, 300nm, 400nm, 500nm or a range consisting of any two thereof.

[0102] In some embodiments, two adjacent protrusions 102 respectively form a first projection and a second projection, the first projection has a first circumscribed circle, the second projection has a second circumscribed circle, the distance between the center of the first circumscribed circle and the center of the second circumscribed circle is L1, and the distance between the first projection and the second projection is L2, and L1 and L2 satisfy the relationship: L1 / L2=1.05~3, preferably, L1 / L2=1.1~2.

[0103] L1 / L2 can reflect the density of the protrusions 102. Setting L1 / L2 in the above range can form a suitable distance between the protrusions 102, ensure the infiltration effect of the electrolyte, thereby ensuring the cycle life of the battery, and also prevent the positive electrode sheet 100 from breaking. In specific design, L1 / L2 can be 1.05, 1.1, 1.3, 1.5, 1.7, 2, 2.5, 3 or any two of them.

[0104] In some specific embodiments, L1=3mm-10mm, preferably, L1=2mm-8mm; and / or, L2=0.5mm-8mm, preferably, L2=1mm-4mm.

[0105] When the distance between the convex portions 102 and the convex portions 102 is less than 2 mm, the convex points of the processing roller are too dense, the extension of the positive electrode sheet 100 cannot meet the density of the convex portions 102, and the height of the convex portions 102 cannot meet the requirements, the deformation space of the positive electrode sheet 100 is small, and the positive electrode sheet 100 is easy to break. When the distance between the convex portions 102 and the convex portions 102 is greater than 8 mm, the convex points of the processed roller are too sparse, the convex portions 102 are too dispersed, and the support area of ​​the convex portions 102 is insufficient, so that the electrolyte infiltration effect cannot be achieved. In the embodiment of the present application, by limiting the ratio of L1 / L2, the density of the convex points can be guaranteed, thereby providing sufficient support force for the electrode sheet, so that the positive electrode sheet 100 has sufficient deformation space to alleviate the expansion of the negative electrode sheet 200.

[0106] In some embodiments, the protrusion 102 has a circumscribed sphere, which includes an outer surface. A flat area is formed between two adjacent protrusions 102. The spherical radius of the outer surface is R1. The distance between the top of the protrusion 102 and the flat area is R3. R3 satisfies the relationship: R3<R1. Preferably, R3<1 / 5R1.

[0107] The circumscribed ball is an ideal shape of the protrusion 102. It is understandable that when the positive electrode sheet 100 is processed to form the concave-convex area 101, due to the processing method, process and error, the protrusion 102 generally does not present an absolutely regular shape similar to the above-mentioned circumscribed ball. For example, when the protrusion 102 is formed by rolling, the protrusion 102 will be squeezed during the rolling process, thereby causing the electrode sheet to deform or extend, so that the protrusion 102 will be relatively flattened, thereby resulting in R3<R1. In the above embodiment, the process can be simplified by controlling R3<1 / 5R1, and at the same time, the basic performance of the positive electrode sheet 100 after the concave-convex area 101 is formed can be guaranteed.

[0108] In some embodiments, the surface area of ​​the outer surface is Q1, and the projection area of ​​the outer surface formed on the positive electrode collector 110 along the thickness direction of the electrode sheet is S1. The circumscribed sphere also includes an inner surface, and the surface area of ​​the inner surface is Q2. The projection area of ​​the inner surface formed on the positive electrode collector 110 along the thickness direction of the electrode sheet is S2. Q1 and Q2 satisfy: Q1 / Q2=1.02~1.21, and / or S1 and S2 satisfy: S1 / S2=1.02~1.21.

[0109] By setting the above relationship, the volume of the protrusion 102 can be reasonably controlled, which is conducive to achieving a balance between the cycle performance, energy density, and structural stability of the positive electrode sheet 100, and can also provide space for the expansion of the negative electrode sheet 200 to prevent the negative electrode sheet 200 from breaking and other adverse consequences. In specific design, Q1 / Q2 can be 1.02, 1.05, 1.07, 1.12, 1.15, 1.19, 1.21 or a range consisting of any two thereof, and S1 / S2 can be 1.02, 1.05, 1.07, 1.12, 1.15, 1.19, 1.21 or a range consisting of any two thereof.

[0110] In some embodiments, the sum of the projected areas of the protrusions 102 on the positive electrode current collector 110 is S11, the area of ​​the positive electrode sheet 100 is S, and S11 and S satisfy the relationship: 0.02≤S11 / S≤0.85.

[0111] S11 / S can reflect the density of the protrusions 102 on the positive electrode current collector 110. When the S11 / S value is small, the number of protrusions 102 is small, and it is difficult to achieve the purpose of improving the cycle life and energy density. When the S11 / S value is large, the number of protrusions 102 is large, which easily causes the positive electrode sheet 100 to wrinkle, deform, or even break. In the above embodiment, setting S11 / S in the above range is beneficial to prevent damage to the positive electrode sheet 100 on the basis of improving the cycle life and energy density. In the specific design, S11 / S can be 0.02, 0.04, 0.1, 0.2, 0.32, 0.4, 0.5, 0.6, 0.7, 0.85 or a range consisting of any two of them.

[0112] In some embodiments, please refer to Figure 2 The positive electrode active material layer 120 also includes a tab region 104 and an end avoidance region 105, the tab region 104 is located on at least one side of the concave-convex region 101 along the width direction of the positive electrode sheet 100, the positive electrode tab 130 is arranged in the tab region 104, and the end avoidance region 105 is located on one side of the concave-convex region 101 along the length direction of the positive electrode sheet 100.

[0113] In combination with the foregoing, the recessed portion 103 region is a region where the convex portion 102 and the recessed portion 103 are provided. Here, by providing the tab area 104 on one side of the concave-convex region 101, a stable installation environment can be provided for the positive electrode tab 130, which is beneficial to reduce the installation difficulty and process of the positive electrode tab 130, improve the installation stability of the positive electrode tab 130, and prevent the interface deterioration of the positive electrode tab 130 surrounding area caused by the interaction between the positive electrode tab 130 and the positive electrode sheet 100, thereby simplifying the installation of the tab while avoiding problems such as insufficient wetting, interface deterioration, cycle failure and lithium precipitation.

[0114] In some embodiments, the width of the tab region 104 is W2, and W2 satisfies: 1 mm ≤ W2 ≤ 30 mm.

[0115] The tab area 104 is located at the edge of the positive electrode sheet 100 along the width direction, and W2 can represent the proportion of the tab area 104 in the width direction of the positive electrode sheet 100. In specific design, W2 can be 1mm, 5mm, 10mm, 15mm, 20mm, 25mm, 30mm or a range consisting of any two of them. It can be understood that the pole ear area 104 is an area where the protrusion 102 or the recess 103 is not set. When W2 exceeds 30mm, the width of the pole ear area 104 is large enough. Although the pole ear area 104 is conducive to the installation of the positive pole ear 130, correspondingly, the protrusion 102 accounts for a small proportion on the positive electrode sheet 100, which will cause the electrolyte to have insufficient liquid storage in the pole ear area 104, which may easily cause poor wetting and even lithium precipitation. When W2 is less than 1mm, the edge of the positive electrode sheet 100 in the width direction may have abnormal structures such as bending, unevenness, and wavy edges, which is not conducive to correcting the positive electrode sheet 100 by laser during the production process, and may cause the negative electrode sheet 200 to cover the positive electrode sheet 100 poorly. Therefore, the embodiment of the present application sets W2 within the above-mentioned size range to control the abnormal structure formed at the edge of the positive electrode sheet 100, and at the same time ensure the wetting of the electrolyte.

[0116] A pole lug is provided in the pole lug region 104 , and the distance between the pole lug and the concave-convex region 101 in the width direction is W1 , and W1 satisfies: 1 mm≤W1≤5 mm.

[0117] In the specific design, W1 can be 1mm, 2mm, 3mm, 4mm, 5mm or a range consisting of any two of them. It can be understood that when W1 exceeds 5mm, the space between the protrusion 102 and the pole ear is larger, and the positive pole ear 130 can be easily installed, but it will affect the number of protrusions 102, thereby affecting the above-mentioned basic functions of the positive electrode sheet 100, which is not conducive to the infiltration of the electrolyte and the avoidance of lithium precipitation problems. When W1 is less than 1mm, the space between the protrusion 102 and the positive pole ear 130 is smaller, and the installation difficulty of the positive pole ear 130 is increased. The number of protrusions 102 is increased, which is conducive to the infiltration of the electrolyte and the avoidance of lithium precipitation problems. Therefore, the embodiment of the present application sets W1 within the above-mentioned size range, which can ensure the basic performance of the positive electrode sheet 100 on the basis of simplifying the installation of the positive pole ear 130.

[0118] The end avoidance area 105 is a structure on the positive electrode sheet 100 corresponding to the single-sided area 107 . The single-sided area 107 here refers to a position where the positive active material layer 120 is disposed on one side of the positive electrode current collector 110 and the positive active material layer 120 is not disposed on the other side.

[0119] Figure 5 A side view of a positive electrode sheet 100 provided according to an embodiment of the present application is shown.

[0120] Can be combined with reference Figure 2 and Figure 5 The positive electrode sheet 100 includes a double-sided area 106 and a single-sided area along its length direction, wherein the double-sided area 106 indicates that the positive electrode sheet 100 is provided with a positive electrode active material layer 120 on both sides of the positive electrode collector 110, and the single-sided area 107 only has a positive electrode active material layer 120 on one side of the positive electrode collector 110, and the concave-convex area 101 is formed in the double-sided area 106.

[0121] In some embodiments, a head end 108 and a tail end 109 are formed along the length direction of the positive electrode sheet 100, and the end space avoidance area 105 includes a first space avoidance area 1051 located at the head end 108 and a second space avoidance area 1052 located at the tail end 109, wherein the dimension of the first space avoidance area 1051 along the length direction is A, and the dimension of the second space avoidance area 1052 along the length direction is B, A satisfies: 1mm≤A≤5mm, and B satisfies: 100mm≤B≤800mm.

[0122] In the specific design, e can be 1mm, 2mm, 3mm, 4mm, 5mm or a range consisting of any two of them. It can be understood that when e exceeds 5mm, the structural stability of the inner area of ​​the core structure can be improved, but it is not conducive to wetting. When e is lower than 1mm, the structural stability of the inner area of ​​the core structure is reduced, but the wetting amount can be increased. Therefore, the embodiment of the present application can achieve a balance between the structural stability and the wetting amount of the inner area of ​​the core structure by setting e within the above-mentioned size range.

[0123] In specific design, B can be 100mm, 200mm, 300mm, 400mm, 500mm, 600mm, 700mm, 800mm or a range consisting of any two of them. When the size B of the tail avoidance zone is in the range of 100mm to 800mm, the second avoidance zone 1052 has a suitable length for tailing, which improves the connection stability of the outside of the core structure, thereby making the entire battery have good winding stability, and making the distribution range of the protrusions 102 adjacent to the outer circle appropriate, thereby providing support for the winding units in the outer circle and improving the extrusion problem of the outer circle of the core structure. When B is less than the lower limit of 100mm, the size of the second avoidance zone 1052 is too small, and the distance from the protrusion 102 in the length direction of the entire pole piece to the edge of the entire pole piece is too small, making it difficult to improve the packaging stability at the end of the core structure. When D is greater than the upper limit of 500 mm, the second air avoidance area 1052 is too large and occupies too large an area, resulting in insufficient distribution area of ​​the protrusions 102 and poor support effect of the protrusions 102, making it difficult to improve the wetting effect of the electrolyte.

[0124] The battery provided by the present invention and its application will be specifically introduced through specific embodiments below.

[0125] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0126] The present application is further described below by taking the electrode assembly of a lithium-ion battery as an example and combining specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0127] In each embodiment and comparative example of the present application, the following method is used to prepare a lithium ion battery and test the performance of the lithium ion battery:

[0128] 1. Preparation method of lithium-ion battery

[0129] 1. Preparation of positive electrode sheet 100

[0130] (Lithium cobalt oxide + Li2NiO2), conductive carbon black (SP), and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97 (the weight of Li2NiO2 accounts for 1% of the weight of lithium cobalt oxide): 1:2, and N-methylpyrrolidone (NMP) is added and stirred evenly to prepare a positive electrode slurry. The positive electrode slurry is coated on the front and back surfaces of an aluminum foil. After baking and rolling, a positive electrode sheet 100 with a thickness of 100 μm is obtained. The positive electrode sheet 100 is embossed from the A side to the C side by a roller to obtain a circular protrusion 102, wherein the diameter R of the protrusion 102 is 2000 μm, the distance L between the protrusions 102 and the protrusions 102 is 2000 μm, and the height h of the vertex of the protrusion 102 from the surface of the positive electrode active material layer 120 is 20 μm.

[0131] 2. Preparation of negative electrode sheet 200

[0132] The silicon-carbon doped negative electrode active material is mixed with conductive carbon black (SP), carboxymethyl cellulose lithium (CMC-Li), and polyacrylic acid (PAA) in a mass ratio of 97 (the weight of silicon and carbon accounts for 5% of the weight of graphite): 0.4: 0.1: 2.5, and deionized water is added to prepare a negative electrode slurry. The negative electrode slurry is coated on the front and back surfaces of the carbon-coated copper foil. After baking and rolling, a negative electrode sheet 200 with a thickness of 110 μm is obtained. A certain position of the negative electrode sheet 200 has a groove of fixed size, and the copper-plated nickel pole ear is welded in this groove by laser or ultrasonic welding.

[0133] 3. Preparation of core structure

[0134] After being cut and produced, the positive electrode sheet 100 and the negative electrode sheet 200 are wound with the separator 300 to form a winding core structure.

[0135] 4. Battery assembly

[0136] The core structure is packaged, baked, injected, formed, sealed, sorted and OCV to obtain a battery. The electrolyte injected in the injection can be a conventional electrolyte, and the lithium salt is LiFP6.

[0137] 2. Performance test of lithium-ion batteries

[0138] 1. K value

[0139] After the battery is stored in a 45℃ high temperature room for 48 to 60 hours, take out the battery and place it in a 25℃ constant temperature room for 24 hours to test the battery voltage V1. Place it in a 25℃ constant temperature room for 72 to 96 hours to test the voltage V2, where the voltage drop is (V1-V2) / interval between two tests.

[0140] 2. Cycle life at 25℃

[0141] In an environment of 25°C, the electrode assembly is charged at a constant current of 2C / 5C to the full charge voltage (the battery design maximum voltage is 4.5V), and then charged at a constant voltage at the maximum voltage until the current is 0.02C, and then discharged at a constant current of 0.5C until the final voltage is 3.0V, and the discharge capacity of the first cycle is recorded. After that, the above steps are repeated for charging and discharging cycles, and the number of cycles N when the cycle capacity retention rate begins to be less than or equal to 80% is recorded.

[0142] Cycle capacity retention rate = (discharge capacity at the Nth cycle / discharge capacity at the first cycle) × 100%.

[0143] 3. Expansion rate of 1000T cycle at 25℃

[0144] Keep it in a constant temperature room or incubator at 25℃ for 2H, 1C constant current and constant voltage to the upper limit voltage, 0.05C until the cell thickness is h1, let it stand for 10min, then discharge it at 0.5C to 3.0V, cycle 1000T, then 1C constant current and constant voltage to the upper limit voltage, 0.05C until the cell thickness is h2, h2 / h1 is the expansion rate of 25℃ cycle 1000T

[0145] 4. Probability of pole piece fracture

[0146] In a 45℃ constant temperature room, 1C constant current and constant voltage were applied to the upper limit voltage, 0.05C was cut off, and the battery was left to stand for 10 minutes. Then, the battery was discharged at 0.5C to 3.0V. After 600T cycles, 10 pieces were disassembled and the number of broken electrodes was counted.

[0147] Table 1 shows various parameters of Examples 1 to 5, Comparative Example 1, Comparative Example 2, and Comparative Example 3, and the experimental results are shown in Table 2.

[0148] Table 1

[0149] Example h ρ h / ρ R L L / R L / R / ρ D D*h / R Embodiment 1 20 2% 1000 2000 2000 1 50 4 0.04 Comparative Example 1 20 1% 2000 2000 2000 1 100 4 0.04 Comparative Example 2 20 10% 200 2000 2000 1 10 4 0.04 Embodiment 2 3 6% 50 2000 2000 1 16.66667 4 0.006 Comparative Example 3 40 1.1% 3636.364 3000 2000 0.666667 60.60606 4 0.053333 Embodiment 3 5 1.1% 454.5455 1000 3000 3 272.7273 4 0.02 Embodiment 4 40 2% 2000 1000 2000 2 100 3 0.12 Embodiment 5 3 2% 150 3000 2000 0.666667 33.33333 4.5 0.0045

[0150] Table 2

[0151]

[0152]

[0153] The following conclusions can be drawn from the analysis of Tables 1 to 4:

[0154] 1) By comparing Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the structural stability of the positive electrode sheet can be changed by changing the weight loss rate. When the weight loss rate is small, the structural stability of the positive electrode sheet is poor and the problem of powder falling easily occurs. When the weight loss rate is large, the positive electrode sheet is brittle and easy to break. Maintaining the weight loss rate at 1.1% to 6% can ensure the structural stability of the positive electrode sheet, prevent the positive electrode sheet from falling and other problems, and prevent the positive electrode sheet from being damaged in the process of forming the concave and convex area on the basis of ensuring the energy density.

[0155] By comparing Example 2 and Comparative Example 3, it can be seen that h / ρ is too small, the protrusion height is small, the electrolyte storage space is small, and the electrolyte content is low, which affects the battery life;

[0156] 2) h / ρ is too large. At this time, the positive electrode binder content is low, and the positive electrode paste is easy to fall off, affecting the service life of the battery cell. At the same time, the protrusion height is too large, the extrusion stress on the positive electrode sheet is large, and the positive electrode sheet is more likely to break.

[0157] By comparing Examples 1 to 5 and Comparative Examples 1 to 3, it can be seen that when L / R / ρ is set to satisfy: 10<L / R / ρ<1000, L / R / ρ is too small, the adhesive content is high, the positive electrode sheet becomes brittle, the flexibility of the electrode sheet deteriorates, and the embossing can easily lead to the breakage of the positive electrode sheet; L / R / ρ is too large, the embossing area is sparse, the liquid storage capacity deteriorates, the electrolyte content is reduced, and the service life of the battery cell is significantly reduced; when the comprehensive condition of 10<L / R / ρ<1000 is met, the battery has a longer service life, and there is no risk of electrode sheet breakage, thereby ensuring the safety performance of the battery.

[0158] By comparing Examples 1 to 5 and Comparative Examples 1 to 3, it can be seen that when D*h / R is set to satisfy: 0.004<D*h / R<0.12, D*h / R is too large, the positive electrode sheet is compacted to a large extent, the flexibility of the electrode sheet is poor, and the greater the protrusion height, the easier the electrode sheet is to break; when D*h / R is too small, the positive electrode sheet is compacted to a small extent, which is not conducive to improving the overall energy density of the battery cell. At the same time, it has a small protrusion height, and the electrolyte storage capacity is poor, which affects the battery life; when the comprehensive condition of 0.004<D*h / R<0.12 is met, the battery as a whole has a higher energy density and a longer service life;.

[0159] In the description of the present application, it should be understood that the terms "including" and "having" and any variations thereof used in the embodiments of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or apparatuses.

[0160] Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed", etc. should be understood in a broad sense, for example, it can be a fixed connection, it can also be a detachable connection, or it can be integrated; it can be directly connected, or it can be indirectly connected through an intermediate medium, it can make the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In addition, the terms "first", "second", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.

[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active material layer arranged on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material. The positive electrode active material layer includes a concavo-convex region, wherein the concavo-convex region includes a plurality of concave portions and convex portions arranged corresponding to the concave portions. In a nitrogen environment, the weight loss rate of the positive electrode active material layer in the temperature range from 35° to 450° C. is ρ, and the ρ satisfies: 1.1% to 6%.

2. The positive electrode sheet according to claim 1, characterized in that: The height of the vertex of the protrusion from the surface of the positive electrode active material layer is h, and h and ρ satisfy the relationship: 50<h / ρ<3600, and / or h=3um~40um.

3. The positive electrode sheet according to claim 2, characterized in that: The diameter of the concave portion is R, the distance between two adjacent concave portions is L, and R, L, and ρ satisfy the relationship: 10<L / R / ρ<1000, and / or R=1000um~5000um, and / or L=1500um~5000um.

4. The positive electrode sheet according to claim 3, characterized in that: The compaction density of the positive electrode sheet is D, and D, h, and R satisfy the relationship: 0.004<D*h / R<0.12, and / or D=3g / cm 3 ~4.5g / cm 3 .

5. The positive electrode sheet according to claim 1, characterized in that: The number of the convex parts or the concave parts in the concave-convex region per unit area is N / cm 2 , said N=2~25, preferably, said N=4~15.

6. The positive electrode sheet according to claim 1, characterized in that: The positive electrode active material layer includes a conductive agent including single-walled carbon nanotubes extending into the positive electrode active material in the top of the convex portion.

7. The positive electrode sheet according to claim 3, characterized in that: The two adjacent convex parts respectively form a first projection and a second projection, the first projection has a first circumscribed circle, the second projection has a second circumscribed circle, the distance between the center of the first circumscribed circle and the center of the second circumscribed circle is L1, the distance between the first projection and the second projection is L2, and L1 and L2 satisfy the relationship: L1 / L2=1.05~3, preferably, L1 / L2=1.1~2.

8. The positive electrode sheet according to claim 7, characterized in that: The L1=3mm-10mm, preferably, the L1=2mm-8mm; And / or, L2=0.5mm~8mm, preferably, L2=1mm~4mm.

9. The positive electrode sheet according to claim 3, characterized in that: The convex portion has a circumscribed sphere, the circumscribed sphere includes an outer surface, a straight region is formed between two adjacent convex portions, the spherical radius of the outer surface is R1, and the distance between the top of the convex portion and the straight region is R3, and R3 satisfies the relationship: R3<R1, preferably, R3<1 / 5R1.

10. The positive electrode sheet according to claim 9, characterized in that: The surface area of ​​the outer surface is Q1, and the projected area of ​​the outer surface formed on the positive electrode collector along the thickness direction of the pole piece is S1. The circumscribed sphere also includes an inner surface, and the surface area of ​​the inner surface is Q2. The projected area of ​​the inner surface formed on the positive electrode collector along the thickness direction of the pole piece is S2. Q1 and Q2 satisfy: Q1 / Q2=1.02~1.21, and / or S1 and S2 satisfy: S1 / S2=1.02~1.

21.

11. The positive electrode sheet according to claim 1, characterized in that: The sum of the projected areas of the protrusions on the positive electrode current collector is S11, the area of ​​the positive electrode sheet is S, and S11 and S satisfy the relationship: 0.02≤S11 / S≤0.

85.

12. The positive electrode sheet according to any one of claims 6 to 11, characterized in that: The single-walled carbon nanotubes are interwoven to form a mesh structure, and the positive electrode active material on the top of the protrusion is wrapped in the mesh structure.

13. The positive electrode sheet according to claim 12, characterized in that: The diameter of the single-walled carbon nanotube is 1nm~1000nm, and the length is 1um~100um; and / or the mass percentage of the single-walled carbon nanotube is 0.5%~5% based on the total mass of the positive electrode active material layer; and / or the thickness of the single-walled carbon nanotube on the positive electrode active material layer is 10nm~500nm.

14. The positive electrode sheet according to claim 1, characterized in that: The positive electrode active material includes a binder, and the mass percentage of the binder is: 1-5wt% based on the total mass of the positive electrode active material layer; and / or the binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.

15. A battery, characterized in that: The invention comprises a separator, a negative electrode sheet and a positive electrode sheet according to any one of claims 1 to 14, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the separator, the positive electrode sheet and the negative electrode sheet are wound along the length direction of the positive electrode sheet to form a winding core structure.

16. The battery according to claim 15, characterized in that The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer comprises a silicon-carbon composite material and / or a silicon-oxygen composite material.

17. The battery according to claim 15, characterized in that The dimension of the convex portion along the thickness direction of the positive electrode sheet is h3, and the dimension of the concave portion along the thickness direction of the positive electrode sheet is h4, and the h3 and h4 satisfy the relationship: h3 / h4=0.2~1.